Brain and Human Body Modeling 2020 Computational Human Models Presented at EMBC 2019 and the BRAIN Initiative® 2019 Meeting - Makarov, Sergey N.; Noetscher, Gregory M.; Nummenmaa, Aapo (Springer International Publishing : Imprint: Springer, 2021)
This open access book describes modern applications of computational human modeling in an effort to advance neurology, cancer treatment, and radio-frequency studies including regulatory, safety, and wireless communication fields. Readers working on any application that may expose human subjects to electromagnetic radiation will benefit from this book's coverage of the latest models and techniques available to assess a given technology's safety and efficacy in a timely and efficient manner. Describes computational human body phantom construction and application; Explains new practices in computational human body modeling for electromagnetic safety and exposure evaluations; Includes a survey of modern applications for which computational human phantoms are critical.